Post-apartheid Speculative Fiction and the South African City - Roux, Rowan (Department of English Language and Literature, 2021)
This thesis examines the role that speculative fiction plays in imagining the city spaces of the future. Considering the rapid pace of change that has marked post-apartheid South Africa as an impetus for emerging literary traditions within contemporary South African speculative fiction, the argument begins by sketching the connections between South Africa's transition to democracy and the emerging speculative texts which mark this period. Positioning speculative fiction as an umbrella term that incorporates a wide selection of generic traditions, the thesis engages with dystopian impulses, science fiction, magical realism and apocalyptic rhetoric. Through theoretical explication, close reading, and textual comparison, the argument initiates a dialogue between genre theory and urban theory as a means of (re)imagining and (re)mapping the city spaces of post-apartheid Cape Town and Johannesburg.